1987
DOI: 10.1242/dev.101.4.877
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of mRNA prevalence and expression of B1 and B2 transcripts in early mouse embryos

Abstract: Considerable evidence indicates that the 2-cell stage is a critical period of mouse embryo development when a transition from maternal to zygotic genomic control takes place. The overall changes in the structure of the mRNA population as a result of this transition were explored using a random cDNA library of 69 clones derived from late 2-cell embryos. The prevalence of the cloned sequences was analysed by dot hybridization of the cDNA clones with labelled cDNA probes synthesized to poly(A)+ RNA from different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(4 citation statements)
references
References 73 publications
(72 reference statements)
1
3
0
Order By: Relevance
“…As expected, MERVL elements were the TEs most frequently upregulated at this stage with 53% (1,382/2,589) of the upregulated TE loci being annotated as MERVL, while they represent only 1% of the total TEs in the murine genome ( Figure 2B ; Supplementary Figure S2A , p < 2.2e-16). In addition, in line with previous evidence ( Taylor and Pikó, 1987 ; Bachvarova, 1988 ; Peaston et al, 2004 ), the upregulated TEs resulted enriched also in MaLR (observed 19%, expected 12%, p < 2.2e-16) and B2 elements (observed 13%, expected 10%, p < 2.2e-16) ( Figure 2B ). The remaining upregulated TEs were mostly old LINE-1s (not belonging to A, G f and T f subfamilies), ERVs (ERVK and ERV1) and SINE elements (Alu and B4) ( Figure 2B ; Supplementary Figure S2A ).…”
Section: Resultssupporting
confidence: 91%
“…As expected, MERVL elements were the TEs most frequently upregulated at this stage with 53% (1,382/2,589) of the upregulated TE loci being annotated as MERVL, while they represent only 1% of the total TEs in the murine genome ( Figure 2B ; Supplementary Figure S2A , p < 2.2e-16). In addition, in line with previous evidence ( Taylor and Pikó, 1987 ; Bachvarova, 1988 ; Peaston et al, 2004 ), the upregulated TEs resulted enriched also in MaLR (observed 19%, expected 12%, p < 2.2e-16) and B2 elements (observed 13%, expected 10%, p < 2.2e-16) ( Figure 2B ). The remaining upregulated TEs were mostly old LINE-1s (not belonging to A, G f and T f subfamilies), ERVs (ERVK and ERV1) and SINE elements (Alu and B4) ( Figure 2B ; Supplementary Figure S2A ).…”
Section: Resultssupporting
confidence: 91%
“…S5a). B1 is abundantly expressed 36 and was indicated to play critical roles in mouse early embryos. 34 B1 was preferentially present near 2-8C gene promoters, consistent with previous work, 37 and correlated with NR5A2 binding at the 2C and 8C stages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S 9a ). B1 was abundantly expressed 42 and was indicated to play critical roles in mouse early embryogenesis. 40 B1 was preferentially present near 2–8C gene promoters, consistent with previous work, 43 and correlated with NR5A2 binding at the 2C and 8C stages (Fig.…”
Section: Resultsmentioning
confidence: 99%